KONSEP KAFAâAH DALAM PERNIKAHAN MENURUT ISLAM (Kajian Normatif, Sosiologis dan Historis ) - Fatimah, Siti (LP3M STAI DARUSSALAM LAMPUNG, 2014)
Marri a geis a way chosenby Godas away forhumansto breedandthe preservation fhis life, aftereach pairhad beenready to dotherolein realizingthe purpose of marriage. The purpose ofmarriageis the creation ofa familythat is Sakinah, which covered mawadah warahmah. Many ways can be doneto realize the purpose of marriage, one way todetermine. The prospective husband and wifeare good can didate is the concept kafaah. But the way is not akey, but most can not determine whether or not the family in later life. Problems kafaah actually there and a debate among scholarssect, opinion among the Hanafi school is more about kafaah discussin detail other thans chool, because the suspectaccording to the Hanafi school because cosmopolite kafaah born people living in Iraq, from diverse social backgrounds so that the Hanafi school considers importantin terms ofsocial kafaah (Sosial Equelity).Â kafaah theory those becomes inevitable. As with the Maliki school that develop din the Hijaz and Medina were not important kafaah in terms ofsocial, religious and only put forward in choosing a husband and wife. Shafiâi and Hanbali found the kafaah flexibleor are presentin adapted local customs. Kafaah influencerelation to the purpose of marriage, it turns out this kafaah segnifikan has influence with the achievement of the purpose of marriage, bothin terms of religion kafaah (Religious Equelity) and insocial terms (Sosial Equelity).